A Farewell to Alms: A Brief Economic History of the World - Heller, Henry (Labour / Le Travail, 2009)
The article reviews the book, "A Farewell to Alms: A Brief Economic History of the World," by Gregory Clark.
Keywords: BOOKS – Reviews; CLARK; Gregory; 1957-; Economic history; FAREWELL to Alms: A Brief Economic History of the World; A (Book); Nonfiction